PENERAPAN GUGATAN SEDERHANA (SMALL CLAIM COURT) DALAM PENYELESAIAN PERKARA WANPRESTASI DI PENGADILAN NEGERI SELONG - ERNA Purnawati (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2020)
This study aims to determine how the application of a simpleclaim court in the settlement of default cases at Selong DistrictCourt, and to find out what aret the obstacles to a small claimcourt in settling default cases at Selong District Court. Thebenefits of this research are expected to provide input in thedevelopment of legal science,especially in the field of civil lawrelated of the settlement of simple lawsuits, especially theclassification of cases breach of contract. The method used inthis research is empirically legal research. The result showedthat the implementation of Perma Number 2 of 2015 andPerma umber 4 of 2019 concerning Procedures for solvingsimple lawsuits at Selong District Court was carried outeffectively with constraints that were more due to theweakness of the Perma itself internally